1993
DOI: 10.1200/jco.1993.11.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D expression detected by immunohistochemistry has independent prognostic value in axillary node-negative breast cancer.

Abstract: These results indicate that CD expression determined by immunohistochemistry is a powerful prognostic factor in ANN breast cancer. The most significant prognostic information was obtained when CD expression (predicting metastatic activity) was combined with estimate of cell-proliferation rate (S-phase fraction).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
3
9

Year Published

1996
1996
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 11 publications
6
55
3
9
Order By: Relevance
“…One advantage of the meta-analytical approach is that it enables the circumvention of the lack of statistical power as a result of the relatively small sample size of many studies. The choice to carry out this meta-analysis on the prognostic role of cathepsin-D in nodenegative breast cancer patients stems from the following reasons: (1) evidence has been reported about the direct relationship of cathepsin-D with tumour cell invasiveness and metastatic behaviour (Garcia et al, 1990;Pujol et al, 1993;Winstanley et al, 1993;Gion et al, 1995); (2) cathepsin-D has been included among the biological factors potentially useful for discrimination between high-and lowrisk patients to avoid adjuvant overtreatment in the latter group (Bevilacqua et al, 1994); (3) although the negative prognostic role of high cathepsin-D levels in node-negative breast cancer patients has been demonstrated by several authors (Spyratos et al, 1989;Thorpe et al, 1989;Tandon et al, 1990;Kute et al, 1992;Isola et al, 1993), conflicting results have also been reported (Namer et al, 1991;Kandalaft et al, 1993;Janicke et al, 1993;Pujol et al, 1993). Our study demonstrated that elevated cathepsin-D values identify nodenegative breast cancer patients characterized by unfavourable prognosis in terms of disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One advantage of the meta-analytical approach is that it enables the circumvention of the lack of statistical power as a result of the relatively small sample size of many studies. The choice to carry out this meta-analysis on the prognostic role of cathepsin-D in nodenegative breast cancer patients stems from the following reasons: (1) evidence has been reported about the direct relationship of cathepsin-D with tumour cell invasiveness and metastatic behaviour (Garcia et al, 1990;Pujol et al, 1993;Winstanley et al, 1993;Gion et al, 1995); (2) cathepsin-D has been included among the biological factors potentially useful for discrimination between high-and lowrisk patients to avoid adjuvant overtreatment in the latter group (Bevilacqua et al, 1994); (3) although the negative prognostic role of high cathepsin-D levels in node-negative breast cancer patients has been demonstrated by several authors (Spyratos et al, 1989;Thorpe et al, 1989;Tandon et al, 1990;Kute et al, 1992;Isola et al, 1993), conflicting results have also been reported (Namer et al, 1991;Kandalaft et al, 1993;Janicke et al, 1993;Pujol et al, 1993). Our study demonstrated that elevated cathepsin-D values identify nodenegative breast cancer patients characterized by unfavourable prognosis in terms of disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been found that stromal and macrophage-like cells are cathepsin-D positively immunostained in approximately 35% of cases defined as negative according to tumour cell immunoreactions irrespective of the use of monoclonal (Isola et al, 1993) or polyclonal (Domagala et al, 1992) antibodies. However, Roger et al (1994) reported that cytosolic cathepsin-D levels correlated with cathepsin-D expression in cancer cells, and several studies agree with the finding that cathepsin-D contents in stromal and cancer cells are directly correlated (Isola et al, 1993;Eng Tan et al, 1994;Ravdin et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Winstanley et al ( 1993) showed a prognostic difference in patients, depending on node-positive or node-negative status. Another study analysed cathepsin D tumour expression in node-negative cases and found a significantly poorer prognosis regarding relapse-free and overall survival in patients with cathepsin D-expressing tumours (Isola et al, 1993). Kandalaft et al (1993) investigated cathepsin D tumour expression in both node-positive and -negative patients and found only a trend to poor prognosis for overall survival in node-positive cases.…”
Section: Discussionmentioning
confidence: 99%